Risk Factors of Urinary Tract Infections Caused by Extended-Spectrum Β-Lactamase-Producing Escherichia Coli in Inpatients at a Tertiary Hospital In Surabaya, Indonesia - Ishak Samuel Wuwuti; Kuntaman; Eddy Bagus Wasito (Folia Medica Indonesiana, 2022)
Highlights: